Pembatasan Klausul pada Perjanjian Baku dalam Upaya Perlindungan Konsumen melalui Undang-Undang Perlindungan Konsumen - Rahil Sasia Putri Harahap; Fiona Chrisanta (CV Rewang Rencang, 2023)
The contractual legal relationship between business actors and consumers is outlined in a form of a contract. A Standard Contract is a contract in which almost all of the clauses in it have been standardized by one of the parties so that the other party does not have the opportunity to negotiate, suggest or request changes to the clauses in the contract. Thus, consumers often have a weaker position and bargaining power than business actors, making the situation between the parties to the contract unbalanced. Therefore, the Consumers Protection Law allows things that can be regulated in a Standard Contract to protect the position of consumers.